PERANG SALIB (Tinjauan Kronologis dan Pengaruhnya terhadap Hubungan Islam dan Kristen) - Abidin, Zaenal (RIHLAH, 2013)
The Crusades happened because of two factors; due to internal conflicts Europe, namely the dualism Christian denominations; namely the Roman Catholic church with its Eastern Orthodox church with its Byzantine Constantinople, and because of the hatred and fear of Muslims to control their existence. Christian-Muslim relations after the Crusades, it can be said better . Both sides can understand each other and show tolerance and efforts to improve inter-religious harmony , but underneath all of that is still common friction and tension between the two sides . Conflicts with religious issues are considered by some as the shadow and influence of "Crusade". Crusades, physically , always won by the Muslims but non-Muslims physically huge losses, both in economic terms and in terms of civilization. Nevertheless, behind the respective parties may also feel some of the benefits of some important discoveries during the Crusades and afterwards